The Social Origin of the Concept of Truth – How Statements Are Built on Disagreements - von Heiseler, Till Nikolaus (Frontiers in Psychology, 2020)
This paper proposes a social account for the origin of the truth value and the emergence of the first declarative sentence. Such a proposal is based on two assumptions. The first is known as the social intelligence hypothesis: that the cognitive evolution of humans is first and foremost an adaptation to social demands. The second is the function-first approach to explaining the evolution of traits: before a prototype of a new trait develops and the adaptation process begins, something already existing is used for a new purpose. Applied to the emergence of declarative sentences (statements), this suggests something already existing––natural signs (such as indexical objects)––was used for the declarative function and thereby integrated into communication. I show that index display (such as the display of hunting trophies) can imply a conceptual structure similar to that informing the syntax of sentences. The view developed in this paper is broadly consistent with the argumentative theory of Mercier and Sperber, which suggests that reasoning is less adapted to decision making than to social purposes such as winning disputes. In this paper I extend this view to the evaluation of propositions expressed in declarative sentences. According to my proposal, the first declarative sentence emerged as the negation of the (implicit) negation of an implicit statement. Thereby, I suggest that the binary structure of the truth value underlying any declarative sentence is founded on disagreements based on conflicts of interests.